Do Fiscal Multipliers Depend on Fiscal Positions? - Huidrom, Raju; Kose, M. Ayhan; Lim, Jamus J.; Ohnsorge, Franziska L. (World Bank, Washington, DC, 2016)
This paper analyzes the relationship between fiscal multipliers and fiscal positions of governments using an Interactive Panel Vector Auto Regression model and a large data-set of advanced and developing economies. The methodology permits tracing the endogenous relationship between fiscal multipliers and fiscal positions while maintaining enough degrees of freedom to draw sharp inferences. The paper reports three major results. First, the fiscal multipliers depend on fiscal positions: the multipliers tend to be larger when fiscal positions are strong (i.e. when government debt and deficits are low) than weak. For instance, the long-run multiplier can be as large as unity when the fiscal position is strong, while it can be negative when the fiscal position is weak. Second, these effects are separate and distinct from the impact of the business cycle on the fiscal multiplier. Third, the state-dependent effects of the fiscal position on multipliers is attributable to two factors: an interest rate channel through which higher borrowing costs, due to investors' increased perception of credit risks when stimulus is implemented from a weak initial fiscal position, crowd out private investment; and a Ricardian channel through which households reduce consumption in anticipation of future fiscal adjustments.